(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
In this article, the author presents a provocation that seeks to bring together the production of História de lenços e ventos, premiered in 1974, by Teatro Ventoforte, directed by Ilo Krugli, with the advent of Teatro de Objects, which took place in the subsequent decade. Going through the premises of this segment of the Performing Arts, a review of the editing is presented in order to weave a new – decolonial – look at the director’s choices.